The Sub 2-h Official Marathon is Possible: Developing a Drafting Strategy for a Historic Breakthrough in Sports - G. D. Fernandes; Nazir Laureano Gandur; Dioser Santos; Victor Maldonado (Sports Medicine - Open)
Abstract Background Drafting for drag reduction is a tactic commonly employed by elite athletes of various sports. The strategy has been adopted by Kenyan runner Eliud Kipchoge on numerous marathon events in the past, including the 2018 and 2022 editions of the Berlin marathon (where Kipchoge set two official world records), as well as in two special attempts to break the 2 h mark for the distance, the Nike Breaking2 (2017) and the INEOS 1:59 Challenge (2019), where Kipchoge used an improved drafting formation to finish in 1:59:40, although that is not recognized as an official record. Results In this study, the drag of a realistic model of a male runner is calculated by computational fluid dynamics for a range of velocities. The formations employed in the past by Kipchoge, as well as alternative formations, are analyzed and systematically compared with respect to mechanical power. In a quest to show that running an official marathon in under 2 h is possible, the power analysis is extended to the pacers. We developed a simple drafting and pacing strategy that Kipchoge could have used to run the 2022 Berlin marathon in a surprising 1 h, 59 min and 48 s. Conclusions Elite marathon runners can make better use of the pacers to experience reduced drag in races. The associated energy reduction makes it possible to run faster, finishing the race in less time. Using a better drafting strategy and a positive splitting pacing strategy, Kenyan runner Eliud Kipchoge could have broken the sub 2 h barrier in both the 2018 and 2022 editions of Berlin Marathon.